Desarrollo ontogénico de la articulación temporomandibular durante el período fetal - Mejía Pavony, Carlos Alfonso; Salazar Monsalve, Liliana (Revista Estomatología, 1996)
Nineteen fetusses were used to determine mandibular fossa’s changes during TMJ ontogeny in humans. After preparation of histologic especimens, fetusses dissection and clearing techniques, we proceeded to corroborate o verify the general embrionary processes and development of TM.J. during fetal periodo by an observational descriptive work. The investigation permitted to conclude that from third month to birth, the fossa concept can not be applied to TMJ ontogeny because this term in an anatomic funtional characteristic in mature TMJ but not in developing TMJ.